2011
DOI: 10.4103/1463-1741.77210
|View full text |Cite
|
Sign up to set email alerts
|

Symphony orchestra musicians′ use of hearing protection and attenuation of custom-made hearing protectors as measured with two different real-ear attenuation at threshold methods

Abstract: Despite a high level of sound exposure and a fairly large selection of earplugs available, musicians have often been reported to use personal hearing protectors only seldom. For better hearing conservation, it is important to identify and eliminate the causes for the low motivation to use hearing protection. We explored the usage rate of custom-molded musician's earplugs (ER-15) among 15 symphony orchestra musicians with a questionnaire, and measured the attenuation properties of their earplugs with a Real-Ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…There have been some clinical reports that some musicians, and in particular trumpet players, have difficulty using Musicians Earplugs. ™ Huttunen et al (2011) reported actual usage in symphony orchestra musicians ranged from 6% to 52%, depending on country, and that 80% of one group reported complaints that their ER15 earplugs "distorted the timbre and/or dynamics of music in the orchestra." Similarly, Mendes et al (2007) reported only 43.7% of their study group accepted hearing protection.…”
Section: Introductionmentioning
confidence: 99%
“…There have been some clinical reports that some musicians, and in particular trumpet players, have difficulty using Musicians Earplugs. ™ Huttunen et al (2011) reported actual usage in symphony orchestra musicians ranged from 6% to 52%, depending on country, and that 80% of one group reported complaints that their ER15 earplugs "distorted the timbre and/or dynamics of music in the orchestra." Similarly, Mendes et al (2007) reported only 43.7% of their study group accepted hearing protection.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, MEPs do not attenuate musical stimuli in a way that reduces levels equally across frequencies. These results help explain why musicians 1) complain that the ER-15 distorts the timbre of music [9], 2) report the most important factor for non-use is sonority of their own instrument [8], 3) don't like the ER-15 because they change the natural sound of the instrument [12], and 4) can't communicate musically when using the ER-20 [11]. This also offers an important hypothesis regarding why the spectral characteristics of musical output changes when musicians use and perform using ER-15 earplugs [13].…”
Section: Discussionmentioning
confidence: 80%
“…A literature review examining these special claims suggests that musicians rate the use of these products negatively [8][9][10][11][12]. In addition to problems with pressure, pain, and discomfort, musicians report low-usage rates of MEPs due to interference with playing ability, distortion of timbre, sonority, and dynamics of the music they and others are playing.…”
Section: Introductionmentioning
confidence: 99%
“…Flat-attenuation earplugs are designed to reduce many of these issues; however, feedback on flat-attenuation earplugs has also been mixed in studies including musicians as participants. Spectrum and level differences for music produced with and without earplugs have been reported (Kozlowski, Zera, & Mlynski, 2011), as well as distortion while listening (Huttunen, Sivonen, & Poykko, 2011). In contrast, data from Chasin and Chong (1992) have suggested similar spectra for openear measurements of music compared with music spectra measured in ears that are occluded with ER-15 Musician earplugs (as reprinted in Chasin, 1996).…”
mentioning
confidence: 85%